Mimetic Annihilation. Issue 1 (April 2021) - Opelz, Hannes
Abstract : What is the relationship between mimesis, biology and identity? I propose to explore this question here by turning to Alex Garland's 2018 SF film Annihilation . Not least because it is identity that is eponymously annihilated in the film via what could be described as biomimetic processes. At stake in Garland's film is an infinitely refracting mimetic process of genetic mutations and exchanges resulting in a fundamental alteration of human identity. When faced with 'the Shimmer' – the alien life-form causing mysterious transformations in what is called 'Area X' – the film's protagonists are forced to shed their understanding of themselves as irreducibly singular, physically self-contained and conceptually inviolable beings. Revisiting the relationship between deconstruction and dialectics, art and genetics, plasticity and the sublime, the living and death, I argue that Garland's annihilating mimesis reveals itself as a conditio biologica that puts into question our very notions of what constitutes the human.